Tales of the great beasts eaudiobook - Mull, Brandon (Spirit Animals: Special Edition., 2014)
Dive, run, and soar through this exhilarating special edition in the NEW YORK TIMES bestselling series, with a story by WILD BORN author, Brandon Mull. In the world of Erdas, there's a story of four noble animals who sacrificed everything to protect their homes from the ambitions of a mad king. Briggan the Wolf, Uraza the Leopard, Jhi the Panda, and Essix the Falcon. Long before they were spirit animals, the four were still legends—Great Beasts, the most powerful beings to roam the wilds of Erdas. Aided by a brave resistance of humans and animals, they gave their lives to protect the world from a threat more dangerous than any it had seen before: their own kind. Wise and cunning, gentle and ruthless, these are tales of the true heroes and villains in the war that started it all.